EFEKTIFITAS POLA KEMITRAAN INTI-PLASMA DAN PRODUKTIFITAS, USAHA TERNAK AYAM BROILER PETERNAK PLASMA DAN MANDIRI SERTA FAKTOR YANG MEMPENGARUHI DI KABUPATEN SLEMAN - Suwarta Suwarta; Irham Irham; Slamet Hartono (University of Jember, 2010)
This research aims to recognize : (a) effective of partnership Inti-Plasma pattern, (b)productivity business livestock broiler chicken partnership Inti-Plasma pattern and independent, and the factors influence. This research is done in Sleman, DIY. The like of analysis unit primary data is resulted of direct interview with one whose work is to rear cattle broiler chicken sample at 2008 – 2009 year. To recognize effective of partnership inti-plasma pattern, with the method deference of evenly test of : (1) evenly percent of production broiler chicken is sold to company with 100 percents, (2)on the average of production’s price and weft’s price, doc’s price is to be paid by company and plasma with production’s price and weft’s price, doc’s price in contract, and (3) on the average of percent of debt with is to be paid by plasma commensurate with contract. To count of the productivity, with the method to divide of the total production with the wide of stable. To calculation productivity function of business livestock broiler chicken, is used OLS method of natural equalization.The result of research show that : (a) performance of partnership ”inti-plasma” business broiler chicken livestock was effective. The condition mentioned is showed by : (1) all of production is sold to company, (2) the production price and weft price, doc price compatible with contract, and (3)evenly percent of debt is to be paid compatible with contract; (b) productivity business livestock broiler chicken for respectively one whose work is to rear cattle group are : (1) one whose work is to rear cattle plasma 15.75 kg/m2, (2) one whose work is to rear cattle independent 13.78 kg/m2,(3) one whose work is to rear cattle “plasma-inti mandiri” 15.43 kg/m2, and (4) one whose work is to rear cattle ”plasma-inti pabrikan” 16.93 kg/m2. That except, according to part, productivity business livestock broiler chicken is influenced by : (1) amount of doc (0.47458);(2) amount of weft (0.45074); (3) amount of “ovk” (0.03527); (4) age (-0.074361),(5) experience (0.0395); and wide of stable (-0.9803).Keyword : Effective, Partnership Inti-Plasma pattern, Productivity